2023
DOI: 10.1002/ana.26724
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted Brain Functional Status in Patients with Reversible Cerebral Vasoconstriction Syndrome

Abstract: ObjectivesThe aim of this study was to investigate the functional networks in subjects with reversible cerebral vasoconstriction syndrome (RCVS) using resting‐state functional magnetic resonance imaging (rs‐fMRI).MethodsWe prospectively recruited patients with RCVS and healthy controls (HCs) between February 2017 and April 2021. The rs‐fMRI data were analyzed using graph theory methods. We compared node‐based global and regional topological metrics (Bundle 1) and network‐based intranetwork and internetwork con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…The LI was used as a vasoconstriction severity indicator in RCVS [ 3 , 38 ]. Although its correlation with DTI-ALPS index was not significant ( p = 0.446), it was important to evaluate the time-trends of vasoconstriction severity with DTI-ALPS dynamics throughout the disease course (Supplementary Figure 5 in Additional file 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The LI was used as a vasoconstriction severity indicator in RCVS [ 3 , 38 ]. Although its correlation with DTI-ALPS index was not significant ( p = 0.446), it was important to evaluate the time-trends of vasoconstriction severity with DTI-ALPS dynamics throughout the disease course (Supplementary Figure 5 in Additional file 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In our practice, all RCVS subjects were treated with nimodipine upon diagnosis since it was not ethical to leave the patients untreated [ 37 ]. Therefore, despite the fact that the DTI-ALPS index values in acute RCVS between subjects with and without nimodipine were similar and we monitored all the subjects closely to avoid any hypotensive episodes with systolic blood pressure < 100 mmHg, [ 38 ] the effects of nimodipine on the hemodynamics and glymphatics may still exist. In fact, some studies have indicated that the nimodipine could increase glymphatic flow [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation